2018
DOI: 10.1097/prs.0000000000004750
|View full text |Cite
|
Sign up to set email alerts
|

Micro-RNA–Regulated Proangiogenic Signaling in Arteriovenous Loops in Patients with Combined Vascular and Soft-Tissue Reconstructions: Revisiting the Nutrient Flap Concept

Abstract: The authors' findings demonstrate that elevated shear stress triggers proangiogenic signaling pathways in human venous tissue, indicating that arteriovenous loops may have the ability to induce neoangiogenesis in humans. The authors' data corroborate the nutrient flap hypothesis and provide a molecular background for arteriovenous loop-based tissue engineering with potential clinical applications for soft-tissue defect reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…The relative abundance level for each miRNA was calculated using the 2 −ΔΔCT equation [23]. RNU6B small nuclear RNA (snRNA) was used an endogenous reference control for normalization purpose as previously described [12,13,22,[24][25][26][27] and because of its minimum abundance variance between the TS patients and HVs as observed by DataAssist™Software (Applied Biosystems). Correlations were computed using Spearman's regression coefficient and the difference between the groups was analyzed using a Mann-Whitney-U test using GraphPad Prism 7.0.…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance level for each miRNA was calculated using the 2 −ΔΔCT equation [23]. RNU6B small nuclear RNA (snRNA) was used an endogenous reference control for normalization purpose as previously described [12,13,22,[24][25][26][27] and because of its minimum abundance variance between the TS patients and HVs as observed by DataAssist™Software (Applied Biosystems). Correlations were computed using Spearman's regression coefficient and the difference between the groups was analyzed using a Mann-Whitney-U test using GraphPad Prism 7.0.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs/miRs) are non-coding single- stranded small molecule RNAs that exert their biological function by inhibiting the transcription and translation of target genes, via binding to the 3′ non-coding region of the target mRNA (8,9). Previous studies have demonstrated that miRNAs are closely associated with the occurrence and development of numerous tumors, including ovarian cancer, liver cancer, stomach cancer and breast cancer (1013).…”
Section: Introductionmentioning
confidence: 99%
“…< 1.5 in the peripheral blood and the vascular wall of AV loops (POD 10 after loop placement). The complete miRNA expression profiles in vascular AV loop tissue were previously published 10 . ( c,d ) Correlation between miRNA expression profiles in blood and vascular tissue reveals 5 concordantly up-regulated miRNAs ( d , upper right quadrant), 2 concordantly down-regulated miRNAs ( d, lower left quadrant), and 4 discordantly deregulated miRNAs ( d , upper left and lower right quadrants).…”
Section: Resultsmentioning
confidence: 99%
“…The goal of our study was to determine the impact of two-stage AV loop reconstructions on the expression levels of circulating miRNAs and the serum levels of NT-proBNP and copeptin as established cardiac biomarkers, in order to provide guidance for risk stratification, selection of operative technique and timing in microsurgical reconstructions with AV loops. Moreover, we correlated the miRNA signatures from peripheral blood of AV loop patients with previously determined miRNA expression profiles from human venous AV loop tissue 10 to identify systemic perturbations of miRNA expression after AV loop placement across different tissue types.…”
Section: Introductionmentioning
confidence: 99%